Endoscopic Retrograde Cholangiopancreatography on Pediatric Patients: Experience of a Portuguese Adult Gastroenterology Department - Saraiva,Rita Ornelas (2024)
Abstract Introduction: Experience with endoscopic retrograde cholangiopancreatography (ERCP) in the pediatric population is limited. Few medical centers have experts specifically trained in pediatric therapeutic endoscopy. As a result, patients are generally referred to adult endoscopists with high experience in the procedure. The aim of this study was to characterize the experience of an adult endoscopy unit with ERCP on pediatric patients, with a special focus on very young patients. Methods: We retrospectively analyzed indications, technical success rate, final clinical diagnosis, and complica-tions of ERCPs in children <18 years at our tertiary referral hospital center between January 1994 and June 2022. Results: Sixty-five ERCPs were performed on 57 children with a median age of 13 years (range 1-17 years). Eleven ERCPs were performed on 9 patients up to 5 years old. Indications for ERCP were as follows: biliary obstruction (n = 40), mainly due to choledocholithiasis, lithiasic acute pancreatitis (n = 19), recurrent pancreatitis (n = 3), stent extraction (n = 2), and post-operative biliary fistula (n = 1). The cannulation success rate was 95.1%. Therapeutic interventions were performed in 79% of ERCP. All patients were followed up as inpatients. Complications were recorded in two procedures (3.1%), and no procedure-related mortality occurred. Conclusion: In our experience, ERCP in children can be safely performed with high success rates by advanced adult-trained expert endoscopists at a high-volume center.